DRY EYE DISEASE – RISK FACTORS, PATHOGENESIS, DIAGNOSTIC METHODS, CLINICAL MANIFESTATIONS AND TREATMENT – NEW LITERATURE REPORTS - Bartłomiej Trzciński,; Patryk Kowalczyk,; Oliwia Gugała,; Igor Winogrodzki,; Alicja Stryczek-Schlusche,; Aleksandra Magdalena Furczyńska,; Wiktoria Socha,; Aleksandra Gęsińska,; Hanna Paszkiewicz,; Kamil Nowak, (International Journal of Innovative Technologies in Social Science, 2025)
Dry eye syndrome (DED) is a prevalent condition, affecting millions of people worldwide.         The condition is characterised by a multifactorial disorder of the ocular surface, resulting in the loss of the natural protective barrier of the eyes, known as the tear film, and accompanied by more or less characteristic symptoms. The objective of this article is to present a thorough review of the extant scientific literature, incorporating an exhaustive analysis of the pathogenesis, identification of risk factors, and discussion of diagnostic and therapeutic methods, with consideration given to both conventional approaches and the most recent research findings. Despite ongoing research, the etiology of dry eye syndrome remains unclear. However, various factors have been identified as potential risk elements, including age, gender, environmental influences, ethnics origin, and comorbidities, particularly autoimmune diseases. Tear substitutes remain the primary and most commonly used treatment method, but recent scientific research has focused on drugs that are capable of modifying inflammatory processes to a much greater extent. Lifestyle modifications or the use of increasingly available specialised medications have enabled patients to recover. The condition of dry eye syndrome poses significant challenges in the domains of both ophthalmology and numerous other medical specialties. The effective control of the disease will only be possible with a coordinated approach to the following: symptoms, pathogenesis and patient capabilities. Further research into mechanisms and diagnostic methods is imperative, with the potential to significantly improve the quality of life for millions of patients.